PENGARUH TERAPI BACK MASSAGE TERHADAP PENURUNAN TINGKAT NYERI PADA PENDERITA RHEUMATOID ARTHRITIS DI DESA RAJADESA KECAMATAN RAJADESA KABUPATEN CIAMIS TAHUN 2018 - Daniel Akbar Wibowo; Dini Nurbaeti Zen; Yalis Agustina (Universitas Galuh Ciamis, 2019)
Disease that is often complained by the public today one of the pain in the bone, which is better known by the community with rheumatism. Rheumatism or rheumatoid arthritis is a systemic, progressive, chronic and tendonic inflammatory disease of joints and connective tissue symmetrically. One way of management of rheumatoid arthritis pain is back massage therapy. Back Massage is one of the techniques to give massage action on the back with lotions/balm for 10-15 minutes, the warm sensation leads to vasodilation of blood vessels that will improve blood circulation in the area so that the activity of the cell is increased and will reduce pain, increase comfort, reduce muscle tension and improve physical and psychological relaxation. This study aims to determine the effect of Back massage therapy to decrease the pain level of rheumatoid arthritis patients in Rajadesa Village Rajadesa Sub District Ciamis District in 2018. Type of research using Quasi Experiment Design with one group pretest-posttest design. Total sample 48 respondents with total sampling technique. Data collection using experimental method with VDS (Verbal Descriptor Scale) pain rate measurement tool. The result of statistical test by using Linear Regression shows Sig = 0,000 <0,05, t value = 18,935> 2,012. Then Ha is accepted, and the average value before therapy is 3.27 with a standard deviation of 0.818, whereas after therapy is 2.23 with a standard deviation of 0.881, meaning there is the effect of back massage therapy on the decrease of pain level in patients with rheumatoid arthritis. So to reduce pain in patients with rheumatoid arthritis can be given back massage therapy.